2009
DOI: 10.1001/archgenpsychiatry.2009.121
|View full text |Cite
|
Sign up to set email alerts
|

Psychiatric Characteristics Associated With Long-term Mortality Among 361 Patients Having an Acute Coronary Syndrome and Major Depression

Abstract: Severity of MDD measured within a few weeks of hospitalization for ACS or failure of MDD to improve during the 6 months following ACS predicted more than a doubling of mortality over 6.7 years of follow-up. Because persistent depression increases mortality and decreases medication adherence, physicians need to aggressively treat depression and be diligent in promoting adherence to guideline cardiovascular drug therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
121
2
3

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 203 publications
(145 citation statements)
references
References 55 publications
13
121
2
3
Order By: Relevance
“…Although careful risk-benefit analysis is always necessary when antidepressant treatment is proposed, in particular i n infants and a dolescents [9,15], an ECG check is not considered necessary before prescribing sertraline in the absence of a known history of cardiac disease or related risk factors [13]. This is in accordance with early reports in adults with preexisting heart disease [15,16].…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…Although careful risk-benefit analysis is always necessary when antidepressant treatment is proposed, in particular i n infants and a dolescents [9,15], an ECG check is not considered necessary before prescribing sertraline in the absence of a known history of cardiac disease or related risk factors [13]. This is in accordance with early reports in adults with preexisting heart disease [15,16].…”
Section: Discussionsupporting
confidence: 62%
“…SSRIs are generally recommended as first-line psychotropic agents for depressed patients with heart failure [8] and improvement in depression was reported to be asso ciated with improved adherence to cardiovascular drug therapy in adults [9]. However, little is known about the use of SSRIs in y ouths with preexisting cardiac disease, in particular, no cases have been published on the use of SSRIs in adolescents with WPW syndrome.…”
Section: Introductionmentioning
confidence: 99%
“…Our group and others [9][10][11][12][13] have shown that new-onset depression during cardiac hospitalization or immediate posthospitalization was related to greater risk of mortality and cardiac morbidity when compared to historical or recurrent depression. However, recent studies [14] report inconsistent findings. To shed light on this important question, this quantitative review and synthesis tested whether the timeframe of depression was related to greater mortality and cardiac morbidity.…”
Section: Introductionmentioning
confidence: 94%
“…[42][43][44][45][46][47] Severity or persistence of depression following admission for myocardial infarction had been associated with a doubling of mortality during subsequent years. 42,46,48,49 Timing of depression may also have an influence. Past psychiatric history does not appear to be as important as depression at the time of myocardial infarction.…”
Section: Mood Disordersmentioning
confidence: 99%